Anisotropic shock response in oriented omnidirectional TATB supercells based on reactive molecular dynamics simulations - Guan-chen Dong; Jia-lu Guan; Ling-hua Tan; Jing Lv; Xiao-na Huang; Guang-cheng Yang (Energetic Materials Frontiers)
1,3,5-Triamino-2,4,6-trinitrobenzene (TATB) is a highly insensitive energetic material used in applications where extreme safety is required primarily. Ensuring the safe use of TATB as planned relies on research into intrinsic behavior under shock loading, which needs further investigation. Here, we study the shock response in oriented supercells of the highly anisotropic TATB based on reactive molecular dynamics simulations and multi-scale shock technique. Results demonstrate that the mechanical response primarily consists of adiabatic compression and plastic deformation. The system is more susceptible to be compressed rather than plastic deformed when shocked direction to the molecular layer at a 45° angle, resulting in the most obvious initial temperature increase. The chemical reaction pathways are similar in our simulations. Under shock loading, polymerization occurs first and then decomposition begins. However, the overall chemical kinetics response intensifies, as the angle between the shock direction and molecular layer decreases. Nonetheless, the rate of decomposition does not strictly correlate with shock direction. Moreover, clusters evolution shows different reactivity based on shock direction and velocity, which makes anisotropy weak at high shock velocity.